2014
DOI: 10.1160/th13-08-0632
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of thrombocytosis and platelet-lymphocyte ratio as potential prognostic markers in colorectal cancer

Abstract: The aim of the present study was to analyse the preoperative platelet count and the platelet-lymphocyte ratio (PLR) in patients with colorectal cancer (CRC) of different stages and with hepatic metastasis of CRC (mCRC) and to compare these factors as potential prognostic markers. Clinicopathological data of 10 years were collected retrospectively from 336 patients with CRC and 118 patients with mCRC. Both in the CRC and the mCRC group overall survival (OS) was significantly worse in patients who had elevated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
(44 reference statements)
4
40
1
Order By: Relevance
“…[16] As for PLR, owing to the variance in the study design or relatively limited sample sizes, some research showed a decreased survival in patients with elevated PLR, [1724] whereas others did not demonstrate the relationship between prognosis and PLR. [15,2530] Until now, there was no meta-analysis accessing the prognostic utility of PLR in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…[16] As for PLR, owing to the variance in the study design or relatively limited sample sizes, some research showed a decreased survival in patients with elevated PLR, [1724] whereas others did not demonstrate the relationship between prognosis and PLR. [15,2530] Until now, there was no meta-analysis accessing the prognostic utility of PLR in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have focused on the prognostic value of an elevated platelet-to-lymphocyte ratio (PLR) in patients with cancer [8,9]. Although PLR had been widely investigated in terms of their prognostic value on cancer survival outcomes [10,11], there are few literature reporting whether PLR is a predictor of venous thromboembolism in cancer patients. To our knowledge, only one literature reported the clinical value of the PLR at the time of VTE diagnosis, in which Ferroni et al found that PLR can be a predictor for response to anticoagulation and survival [12].…”
Section: Introductionmentioning
confidence: 99%
“…All patients that received adjuvant chemotherapy were treated with a fluoropyrimidine-based regimen, in the form of either single-agent oral capecitabine or intravenous 5-fluorouracil (5-FU), or as combination chemotherapy with FOLFOX (bolus and infusional 5-FU with oxaliplatin). Gene expression analyses have confirmed distinct molecular profiles for colorectal and appendiceal cancer [11,15]. The marked difference in the clinical behavior of these two entities further corroborates their distinct biologies and challenges the dogma of using colorectal cancer regimens for appendiceal cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have found elevated preoperative tumor marker levels (CEA, CA 19-9 and CA125) to be associated with an increased risk of recurrence and reduced survival after complete cytoreductive surgery [9,10]. There is increasing evidence that a systemic inflammatory response is of prognostic value in various cancers [11,12]. Absolute lymphocyte count (ALC) is considered a surrogate marker for the level of immunosuppression and nutritional status of patients and a prognostic factor for survival and recurrence in several cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation